Pengembangan Usaha Homemade Tempe Di Belimbing Kota Padang Provinsi Sumatera Barat - Yenni Del Rosa; Mohammad Abdilla; Nofri Yendra; Anna Marina; Nisya Cesaryani Rahmasari (Jurnal Pengabdian Masyarakat Dharma Andalas, 2023)
Mr. Mukhlis's homemade tempeh business has lacked the touch of appropriate technological information. The turnover was Rp. 1,000,000 per day before the Covid-19 pandemic and Rp. 700,000 per day during the Covid-19 pandemic. The marketing was around the Belimbing market, entrusted to several stalls and regular customers who routinely buy every day. The business prospects for tempe are quite good because the demand for tempe is continuous every day as a type of food that is high in nutritional content and is beneficial for the health of the body. The priority issue for Mr. Mukhlis's homemade tempe business is market share, marketing strategy and product packaging. The method of implementing extension activities is by lecture, discussion and practice methods. The purpose of the activity is for partners to know about market share, marketing strategies and product packaging. The market share of all levels of society is the lower class and upper class of various ages. Marketing strategy by maintaining existing markets and quality, looking for new markets and alternative marketing channels. Product packaging is disposable, primary and flexible.